The Key Role of Exosomes on the Pre-metastatic Niche Formation in Tumors - Yang, Xuyang; Zhang, Yang; Zhang, Yaguang; Zhang, Su; Qiu, Lei; Zhuang, Zixuan; Wei, Mingtian; Deng, Xiangbing; Wang, Ziqiang; Han, Junhong (Frontiers in Molecular Biosciences, 2021)
Exosomes or other extracellular vesicles released from cells play an important role in cell-to-cell communication by transferring bio-information (DNA, coding/non-coding RNA, and proteins), which indicates parental cell status to recipient cells in the extracellular environment. Increasingly, evidence shows that tumor-derived exosomes mediate tumor premetastatic niche (PMN) remodeling to establish a supportive and receptive niche to promote tumor cell colonization and metastasis. Uptake of genetic information by target cells in the extracellular environment triggers epigenetic changes that contribute to PMN formation. Here, we provide a comprehensive overview of the current understanding of exosomes-mediated reprogramming of cells in PMN formation.